A metal and porous ceramic dual-phase composite material and preparation method thereof

By adding metal alloy powder and inorganic pore-forming agent to porous ceramic materials, the metal cermet composite materials are solved, and the problems of low strength and toxicity of existing porous ceramic materials are achieved, achieving high-strength, long-life and environmentally friendly fog Core material.

CN116752025BActive Publication Date: 2025-02-14SHENZHEN JIYOU TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310690788.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-12
Publication Date
2025-02-14
Estimated Expiration
2043-06-12

AI Technical Summary

Technical Problem

The existing porous ceramic atomized core materials have low strength, high sintering temperature, poor membrane-based bonding and short life. The organic pore-forming agent is prone to decomposition during the glue discharge process to produce toxic substances, and the pore size distribution is uneven.

Method used

Using a duplex composite material of metal and porous ceramics, a three-dimensional framework structure of metal and ceramic phase is formed by adding nickel-ferroalloy powder or iron-chromium alloy powder to the ceramic powder, and the hollow microbeads of the metal phase and ceramic phase are used to form an inorganic pore-making agent SiO2-Al2O3 hollow microbead Pores, reduce sintering temperature and increase porosity and through-hole ratio.

Benefits of technology

It significantly improves the strength and life of porous ceramic materials, matches the thermal expansion coefficient of the heating film, improves the use effect and durability of the atomized core, and avoids the toxicity problems of organic pore-forming agents and high sintering temperature.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116752025B_ABST
    Figure CN116752025B_ABST
Patent Text Reader

Abstract

The invention discloses a metal and porous ceramic dual-composite phase composite material and a preparation method thereof, and relates to the field of atomizers. The metal and porous ceramic dual-composite phase composite material comprises the following components per 100 parts by weight: 35-50 parts of ultrafine quartz powder or ultrafine alumina ceramic powder; 3-6 parts of sintering aid; 3-8 parts of metal alloy powder; 3-5 parts of Si powder and / or boron powder; 8-15 parts of low-temperature glass powder; 25-40 parts of inorganic pore-forming agent, wherein the inorganic pore-forming agent is SiO 2 ‑Al 2 O 3 Hollow microspheres; 5-7 parts of polyvinyl alcohol aqueous solution, the mass concentration of the polyvinyl alcohol aqueous solution is 0.9-1.0%. The strength of the metal and porous ceramic dual-composite composite material prepared by the present invention is significantly improved, which can meet the manufacturing and assembly requirements under various composite stress conditions; it forms a metallurgical bond with the heating layer of the thick film printing and the thin film coating, thereby increasing the life of the atomization core and meeting the requirements of high-power atomization; and it uses an inorganic pore-forming agent instead of an organic pore-forming agent, which is more environmentally friendly and improves efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of atomizers, and in particular to a metal and porous ceramic dual-phase composite material and a preparation method thereof. Background Art

[0002] In the atomizer structure, the atomizer core is a very critical component. Currently, the atomizer core often uses porous ceramic materials as the substrate, and a heating film is arranged on the substrate. The atomization matrix absorbed by the substrate is heated by the heating film to achieve the atomization effect.

[0003] Natural diatomite has a large number of pore structures, among which mesopores and macropores have strong adsorption properties and are often used as the main material for porous ceramic substrates of atomizer cores. At present, the main method for preparing porous ceramics is to use diatomite as the main body and add a certain amount of binder and pore-forming agent for sintering. However, porous ceramics prepared from diatomite have low strength, high sintering temperature, poor membrane-base bonding and short life. In addition, most of the existing porous ceramics use organic pore-forming agents for pore formation, which are easy to decompose and volatilize toxic decomposition products during the debinding process. The particle size distribution of the pore-forming agent also has a large range, resulting in uneven pore size distribution after pore formation, and more closed pores and fewer through pores, which affects the use effect of the atomizer core. Summary of the invention

[0004] In order to solve the problems existing in the above-mentioned prior art, the purpose of the present invention is to provide a metal and porous ceramic dual-phase composite material and a preparation method thereof, by metallizing the porous ceramic material, the strength of which is significantly improved, and can meet the manufacturing and assembly requirements under various composite stress conditions.

[0005] The present invention provides the following technical solutions:

[0006] In a first aspect, the present invention provides a metal and porous ceramic dual-composite phase composite material, comprising the following components per 100 parts by weight:

[0007] 35-50 parts of ultrafine quartz powder or alumina ceramic powder;

[0008] 3-6 parts of burning aid;

[0009] 3-8 parts of metal alloy powder;

[0010] 3-5 parts of Si powder and / or boron powder;

[0011] 8-15 parts of low temperature glass powder;

[0012] 25-40 parts of an inorganic pore-forming agent, wherein the inorganic pore-forming agent is SiO2-Al2O3 hollow microspheres;

[0013] 5-7 parts of polyvinyl alcohol aqueous solution, wherein the mass concentration of the polyvinyl alcohol aqueous solution is 0.9-1.0%.

[0014] Furthermore, the inorganic pore-forming agent avoids the problem that the organic pore-forming agent is prone to produce toxic decomposition products during the debinding process, the debinding process is also long and the cost is high. The pores are formed by the self-foaming of hollow microspheres during high-temperature sintering, which can greatly shorten the debinding process, is more economical and environmentally friendly, and the obtained metal and porous ceramic dual-composite phase composite material has a higher proportion of through holes and a larger porosity.

[0015] Furthermore, the SiO2 content in the ultrafine quartz powder is greater than 99%, and the mesh number of the ultrafine quartz powder is less than 300 meshes.

[0016] Furthermore, the purity of the alumina ceramic powder is greater than 99%, and the mesh size of the alumina ceramic powder is less than 300 meshes.

[0017] Furthermore, the sintering aid is selected from at least one of CaF2 and CaCO3. The sintering temperature of quartz sand or alumina can be significantly reduced by adding the sintering aid.

[0018] Furthermore, the metal alloy powder is selected from one of nickel-iron alloy powder and iron-chromium alloy powder; the mesh number of the metal alloy powder is 300-400 meshes. By adding nickel-iron alloy powder or iron-chromium alloy powder to the ceramic powder, a metal phase is formed inside the ceramic, and the three-dimensional skeleton in the matrix is ​​composed of a ceramic phase and a metal phase. Compared with a single ceramic phase, the formation of the metal phase changes the original thermal conductivity and thermal expansion coefficient of the ceramic matrix, so that the performance of the metallized composite material changes from the typical brittleness of the ceramic phase to the toughness of the metal phase, which not only brings a significant improvement in the comprehensive mechanical properties, but also changes the original mechanical adhesion between the heating film and the matrix to a metallurgical bond. The single ceramic phase and the heating film have a huge difference in thermal expansion coefficient, which causes the matrix to break during atomization, and the changes in the thermal conductivity and thermal expansion coefficient of the composite material can better match the heating film and the metallurgical bonding layer formed with the heating film, which can significantly improve the lifespan.

[0019] Furthermore, the metal alloy powder is nickel-iron alloy powder, and the content of Ni in the nickel-iron alloy powder is 50-65wt.%.

[0020] Furthermore, when the metal alloy powder is an iron-chromium alloy powder, the content of Cr in the iron-chromium alloy powder is 50-65wt.%.

[0021] Furthermore, the Si powder and / or boron powder are both in granular or powder form, with a mesh size of 300-400 meshes.

[0022] Furthermore, the Si powder and / or the boron powder can improve the compatibility between the metal alloy powder and the ceramic.

[0023] Furthermore, the Si powder and / or boron powder is preferably Si powder and boron powder, which form NiFeBSi amorphous alloy metal phase or CrFeBSi amorphous alloy metal phase with nickel-iron alloy powder or iron-chromium alloy powder during high-temperature sintering and are connected to the matrix through non-covalent bonds and covalent bonds. After sintering, a continuous metal phase is formed in the three-dimensional skeleton of the porous ceramic. The metal phase and the ceramic phase are interactively combined to form a three-dimensional network skeleton structure of the porous ceramic, which can greatly improve the strength and toughness of the ceramic matrix. At the same time, due to the presence of the continuous metal phase after co-firing, a stable metallurgical bond can be formed between the heating layer and the matrix during subsequent thick film printing or thin film coating, thereby increasing the life of the heating film and also meeting the requirements of high-power atomization for the overall atomization core.

[0024] Furthermore, the low-temperature glass powder has a softening point of 700-900°C.

[0025] In a second aspect, the present invention provides a method for preparing a metal and porous ceramic dual-phase composite material, comprising the following steps:

[0026] S1, pretreatment and powder mixing; high-purity quartz sand or alumina ceramics are dry-milled and then sieved through a 300-mesh sieve to obtain ultrafine quartz powder or alumina ceramics powder, sintering aid, metal alloy powder, Si powder or boron powder, low-temperature glass powder and inorganic pore-forming agent are added to the ultrafine quartz powder or alumina ceramics powder, and then the mixture is fully ball-milled at a low speed to obtain a mixed powder; the mass fraction of SiO2 in the high-purity quartz sand is greater than 99%, the purity of the alumina ceramics is greater than 99%, and the inorganic pore-forming agent is SiO2-Al2O3 hollow microspheres; the steel balls for dry ball milling are zirconia balls, and the material-to-ball ratio is 1:(0.5-1).

[0027] S2, porous ceramic molding; the mixed powder is mixed with a polyvinyl alcohol aqueous solution, stirred and mixed evenly, and then molded by dry pressing to obtain a ceramic green body; the dry pressing molding pressure is 400-600MPa, and the holding time is 5-10min;

[0028] S3, sintering molding; drying the ceramic green body at 70-90 ° C for 4-6 hours, and then at a vacuum degree of 1*10 -1 The temperature is raised at a rate of less than 5°C / min in a vacuum program temperature-controlled furnace below Pa, kept at 1100-1200°C for 0.5-1h, and cooled to room temperature along with the furnace to obtain a metal and porous ceramic dual-composite phase composite material.

[0029] The present invention has the following technical effects:

[0030] 1. The strength of the metallized porous ceramic material of the present invention is significantly improved, and can meet the manufacturing and assembly requirements under various composite stress conditions;

[0031] 2. The metal and porous ceramic dual-phase composite material prepared by the present invention forms a metallurgical bond with the heating layer of thick film printing and thin film coating, which greatly improves the life of the atomizer core and also meets the requirements of high-power atomization;

[0032] 3. The metal and porous ceramic dual-phase composite material of the present invention has a porosity of 50-70%, a pore size of 15-45um, and a flexural strength of 170-250MPa;

[0033] 4. The present invention adopts inorganic pore-forming agent instead of organic pore-forming agent, which is more environmentally friendly and improves efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0035] Figure 1 A process diagram of a method for preparing a metal and porous ceramic dual-phase composite material provided in an embodiment of the present invention. DETAILED DESCRIPTION

[0036] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] It should be understood that when used in this specification and the appended claims, the terms "include" and "comprises" indicate the presence of described features, integers, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components and / or combinations thereof.

[0038] In order to more fully understand the technical content of the present invention, the technical solution of the present invention is further introduced and illustrated in conjunction with specific embodiments below.

[0039] The present invention provides a metal and porous ceramic dual-composite phase composite material, which comprises the following components per 100 parts by weight:

[0040] 35-50 parts of ultrafine quartz powder or alumina ceramic powder;

[0041] 3-6 parts of burning aid;

[0042] 3-8 parts of metal alloy powder;

[0043] 3-5 parts of Si powder and / or boron powder;

[0044] 8-15 parts of low temperature glass powder;

[0045] 25-40 parts of an inorganic pore-forming agent, wherein the inorganic pore-forming agent is SiO2-Al2O3 hollow microspheres;

[0046] 5-7 parts of polyvinyl alcohol aqueous solution, wherein the mass concentration of the polyvinyl alcohol aqueous solution is 0.9-1.0%.

[0047] The present invention also provides a method for preparing a metal and porous ceramic dual-phase composite material, comprising the following steps:

[0048] S1, pretreatment and powder mixing: adding sintering aid, metal alloy powder, Si powder or boron powder, low-temperature glass powder and inorganic pore-forming agent to ultrafine quartz powder or alumina ceramic powder, and then performing low-speed ball milling to fully mix to obtain a mixed powder;

[0049] S2, porous ceramic molding; the mixed powder is mixed with a polyvinyl alcohol aqueous solution, stirred and mixed evenly, and then molded by dry pressing to obtain a ceramic embryo; the dry pressing molding pressure is 400-600MPa, and the holding time is 5-10min;

[0050] S3, sintering molding; drying the ceramic green body at 70-90 ° C for 4-6 hours, and then at a vacuum degree of 1*10 -1 The temperature is raised at a rate of less than 5°C / min in a vacuum program temperature-controlled furnace below Pa, kept at 1100-1200°C for 0.5-1h, and cooled to room temperature along with the furnace to obtain a metal and porous ceramic dual-composite phase composite material.

[0051] In some embodiments, the preparation method of ultrafine quartz powder is: dry-milling high-purity quartz sand with a SiO2 mass fraction of 99% for 2 hours, passing through a 300-mesh sieve, and obtaining ultrafine quartz powder.

[0052] In some embodiments, the preparation method of ultrafine alumina ceramic powder is: dry-milling alumina ceramic with a purity of 99% for 2 hours, passing through a 300-mesh sieve, and obtaining ultrafine alumina ceramic powder.

[0053] In some embodiments, the metal alloy powder is selected from one of nickel-iron alloy powder and iron-chromium alloy powder; the mesh size of the metal alloy powder is 300-400 meshes.

[0054] In some embodiments, the metal alloy powder is nickel-iron alloy powder, and the Ni content in the nickel-iron alloy powder is 50-65wt.%.

[0055] In some embodiments, when the metal alloy powder is an iron-chromium alloy powder, the content of Cr in the iron-chromium alloy powder is 50-65wt.%.

[0056] In some embodiments, the sintering aid is selected from at least one of CaF2 and CaCO3.

[0057] In some embodiments, the SiO2-Al2O3 hollow microspheres have a diameter of 100-200 μm and an impurity content of <1%.

[0058] In some embodiments, the low temperature glass powder has a softening point of 700-900°C.

[0059] In some embodiments, the steel balls used in the dry ball milling are zirconia balls, and the material-to-ball ratio is 1:(0.5-1).

[0060] The embodiments and comparative examples provided by the present invention are as follows:

[0061] Example 1

[0062] A metal and porous ceramic dual-composite phase composite material, comprising the following components per 100 parts by weight:

[0063] 40 parts of ultrafine quartz powder;

[0064] 5 parts of sintering aid CaF2;

[0065] 4 parts of nickel-iron alloy powder, wherein the content of Ni in the nickel-iron alloy powder is 50wt.%;

[0066] 3 parts of Si powder;

[0067] 8 parts of low-temperature glass powder, wherein the softening point of the low-temperature glass powder is 900° C.;

[0068] 35 parts of an inorganic pore-forming agent, wherein the inorganic pore-forming agent is SiO2-Al2O3 hollow microspheres with a diameter of 100 μm;

[0069] 5 parts of polyvinyl alcohol aqueous solution, wherein the mass concentration of the polyvinyl alcohol aqueous solution is 1.0%.

[0070] A method for preparing a metal and porous ceramic dual-phase composite material comprises the following steps:

[0071] 1. Pretreatment and powder mixing;

[0072] The ultrafine quartz powder, sintering aid CaF2, nickel-iron alloy powder, Si powder, low-temperature glass powder and inorganic pore-forming agent are mixed, and the mixed powder is obtained after being fully mixed by low-speed ball milling; the mesh size of the sintering aid CaF2, nickel-iron alloy powder, Si powder and low-temperature glass powder is 300 mesh.

[0073] 2. Porous ceramic molding;

[0074] The mixed powder is mixed with a polyvinyl alcohol aqueous solution, stirred and mixed evenly, and then formed by dry pressing to obtain a ceramic green body;

[0075] 3. Low temperature sintering;

[0076] The ceramic embryo was dried in a drying oven at 85°C for 4 hours, then heated at a rate of 5°C / min in a vacuum program temperature-controlled furnace to 1150°C and kept for 1 hour, and then cooled to room temperature to obtain a metal and porous ceramic dual-phase composite material.

[0077] Example 2

[0078] A metal and porous ceramic dual-composite phase composite material, comprising the following components per 100 parts by weight:

[0079] 40 parts of ultrafine quartz powder;

[0080] 3 parts of sintering aid CaF2;

[0081] 8 parts of nickel-iron alloy powder, wherein the content of Ni in the nickel-iron alloy powder is 50wt.%;

[0082] 3 parts of Si powder;

[0083] 8 parts of low temperature glass powder;

[0084] 32 parts of an inorganic pore-forming agent, wherein the inorganic pore-forming agent is SiO2-Al2O3 hollow microspheres with a diameter of 100 μm;

[0085] 6 parts of polyvinyl alcohol aqueous solution, wherein the mass concentration of the polyvinyl alcohol aqueous solution is 1.0%.

[0086] A method for preparing a metal and porous ceramic dual-phase composite material comprises the following steps:

[0087] 1. Pretreatment and powder mixing;

[0088] The ultrafine quartz powder, sintering aid CaF2, nickel-iron alloy powder, Si powder, low-temperature glass powder and inorganic pore-forming agent are mixed, and the mixed powder is obtained after being fully mixed by low-speed ball milling; the mesh size of the sintering aid CaF2, nickel-iron alloy powder, Si powder and low-temperature glass powder is 300 mesh.

[0089] 2. Porous ceramic molding;

[0090] The mixed powder is mixed with a polyvinyl alcohol aqueous solution, stirred and mixed evenly, and then formed by dry pressing to obtain a ceramic green body;

[0091] 3. Low temperature sintering;

[0092] The ceramic embryo was dried in a drying oven at 85°C for 4 hours, then heated at a rate of 5°C / min in a vacuum program temperature-controlled furnace to 1150°C and kept for 1 hour, and then cooled to room temperature to obtain a metal and porous ceramic dual-phase composite material.

[0093] Example 3

[0094] A metal and porous ceramic dual-composite phase composite material, comprising the following components per 100 parts by weight:

[0095] 35 parts of ultrafine alumina ceramic powder;

[0096] 3 parts of sintering aid CaCO3;

[0097] 6 parts of ferrochromium alloy powder, wherein the Cr content of the ferrochromium alloy powder is 65wt.%;

[0098] 3 parts of boron powder;

[0099] 8 parts of low temperature glass powder;

[0100] 40 parts of an inorganic pore-forming agent, wherein the inorganic pore-forming agent is SiO2-Al2O3 hollow microspheres with a diameter of 100 μm;

[0101] 5 parts of polyvinyl alcohol aqueous solution, wherein the mass concentration of the polyvinyl alcohol aqueous solution is 1.0%.

[0102] A method for preparing a metal and porous ceramic dual-phase composite material comprises the following steps:

[0103] 1. Pretreatment and powder mixing;

[0104] The above-mentioned ultrafine oxidation furnace ceramic powder, sintering aid CaCO3, nickel-iron alloy powder, boron powder, low-temperature glass powder and inorganic pore-forming agent are mixed, and after being fully mixed by low-speed ball milling, a mixed powder is obtained; the mesh size of the sintering aid CaCO3, nickel-iron alloy powder, boron powder and low-temperature glass powder is 400 mesh.

[0105] 2. Porous ceramic molding;

[0106] The mixed powder is mixed with a polyvinyl alcohol aqueous solution, stirred and mixed evenly, and then formed by dry pressing to obtain a ceramic green body;

[0107] 3. Low temperature sintering;

[0108] The ceramic embryo was dried in a drying oven at 90°C for 4 hours, then heated at a rate of 5°C / min in a vacuum program temperature-controlled furnace to 1100°C and kept for 1 hour, and then cooled to room temperature to obtain a metal and porous ceramic dual-phase composite material.

[0109] Example 4

[0110] A metal and porous ceramic dual-composite phase composite material, comprising the following components per 100 parts by weight:

[0111] 50 parts of ultrafine alumina ceramic powder;

[0112] 6 parts of sintering aid CaCO3;

[0113] 3 parts of ferrochromium alloy powder, wherein the Cr content in the ferrochromium alloy powder is 58wt.%;

[0114] 3 parts of boron powder;

[0115] 8 parts of low temperature glass powder;

[0116] 25 parts of an inorganic pore-forming agent, wherein the inorganic pore-forming agent is SiO2-Al2O3 hollow microspheres with a diameter of 200 μm;

[0117] 5 parts of polyvinyl alcohol aqueous solution, wherein the mass concentration of the polyvinyl alcohol aqueous solution is 0.9%.

[0118] A method for preparing a metal and porous ceramic dual-phase composite material comprises the following steps:

[0119] 1. Pretreatment and powder mixing;

[0120] The above-mentioned ultrafine alumina ceramic powder, sintering aid CaCO3, nickel-iron alloy powder, boron powder, low-temperature glass powder and inorganic pore-forming agent are mixed, and after being fully mixed by low-speed ball milling, a mixed powder is obtained; the mesh size of the sintering aid CaCO3, nickel-iron alloy powder, boron powder and low-temperature glass powder is 300 mesh.

[0121] 2. Porous ceramic molding;

[0122] The mixed powder is mixed with a polyvinyl alcohol aqueous solution, stirred and mixed evenly, and then formed by dry pressing to obtain a ceramic green body;

[0123] 3. Low temperature sintering;

[0124] The ceramic embryo was dried in a drying oven at 70°C for 6 hours, then heated at a rate of 5°C / min in a vacuum program temperature-controlled furnace to 1200°C and kept at that temperature for 0.5 hours. The metal and porous ceramic dual-phase composite material was obtained by cooling to room temperature in the furnace.

[0125] Example 5

[0126] A metal and porous ceramic dual-composite phase composite material, comprising the following components per 100 parts by weight:

[0127] 40 parts of ultrafine alumina ceramic powder;

[0128] 3 parts of sintering aid CaF2;

[0129] 5 parts of nickel-iron alloy powder, wherein the content of Ni in the nickel-iron alloy powder is 50wt.%;

[0130] 4 parts of Si powder;

[0131] 15 parts of low temperature glass powder;

[0132] 28 parts of an inorganic pore-forming agent, wherein the inorganic pore-forming agent is SiO2-Al2O3 hollow microspheres with a diameter of 150 μm;

[0133] 5 parts of polyvinyl alcohol aqueous solution, wherein the mass concentration of the polyvinyl alcohol aqueous solution is 0.95%.

[0134] A method for preparing a metal and porous ceramic dual-phase composite material comprises the following steps:

[0135] 1. Pretreatment and powder mixing;

[0136] The ultrafine quartz powder, sintering aid CaF2, nickel-iron alloy powder, Si powder, low-temperature glass powder and inorganic pore-forming agent are mixed, and the mixed powder is obtained after being fully mixed by low-speed ball milling; the mesh size of the sintering aid CaF2, nickel-iron alloy powder, Si powder and low-temperature glass powder is 300 mesh.

[0137] 2. Porous ceramic molding;

[0138] The mixed powder is mixed with a polyvinyl alcohol aqueous solution, stirred and mixed evenly, and then formed by dry pressing to obtain a ceramic green body;

[0139] 3. Low temperature sintering;

[0140] The ceramic embryo was dried in a drying oven at 85°C for 5 h, then heated at a rate of 5°C / min in a vacuum program temperature-controlled furnace to 1150°C and kept for 0.75 h. The metal and porous ceramic dual-phase composite material was obtained by cooling to room temperature in the furnace.

[0141] Example 6

[0142] A metal and porous ceramic dual-composite phase composite material, comprising the following components per 100 parts by weight:

[0143] 40 parts of ultrafine alumina ceramic powder;

[0144] 5 parts of sintering aid CaF2;

[0145] 5 parts of nickel-iron alloy powder, wherein the content of Ni in the nickel-iron alloy powder is 50wt.%;

[0146] 3 parts of Si powder;

[0147] 10 parts of low temperature glass powder;

[0148] 30 parts of an inorganic pore-forming agent, wherein the inorganic pore-forming agent is SiO2-Al2O3 hollow microspheres with a diameter of 150 μm;

[0149] 5 parts of polyvinyl alcohol aqueous solution, wherein the mass concentration of the polyvinyl alcohol aqueous solution is 0.95%.

[0150] A method for preparing a metal and porous ceramic dual-phase composite material comprises the following steps:

[0151] 1. Pretreatment and powder mixing;

[0152] The ultrafine quartz powder, sintering aid CaF2, nickel-iron alloy powder, Si powder, low-temperature glass powder and inorganic pore-forming agent are mixed, and the mixed powder is obtained after being fully mixed by low-speed ball milling; the mesh size of the sintering aid CaF2, nickel-iron alloy powder, Si powder and low-temperature glass powder is 300 mesh.

[0153] 2. Porous ceramic molding;

[0154] The mixed powder is mixed with a polyvinyl alcohol aqueous solution, stirred and mixed evenly, and then formed by dry pressing to obtain a ceramic green body;

[0155] 3. Low temperature sintering;

[0156] The ceramic embryo was dried in a drying oven at 85°C for 5 h, then heated at a rate of 5°C / min in a vacuum program temperature-controlled furnace to 1150°C and kept for 0.75 h. The metal and porous ceramic dual-phase composite material was obtained by cooling to room temperature in the furnace.

[0157] Example 7

[0158] A metal and porous ceramic dual-composite phase composite material, comprising the following components per 100 parts by weight:

[0159] 40 parts of ultrafine quartz powder;

[0160] 6 parts of sintering aid CaF2;

[0161] 4 parts of nickel-iron alloy powder, wherein the content of Ni in the nickel-iron alloy powder is 50wt.%;

[0162] 3 parts of Si powder;

[0163] 2 parts of boron powder;

[0164] 8 parts of low temperature glass powder;

[0165] 30 parts of an inorganic pore-forming agent, wherein the inorganic pore-forming agent is SiO2-Al2O3 hollow microspheres with a diameter of 100 μm;

[0166] 7 parts of polyvinyl alcohol aqueous solution, wherein the mass concentration of the polyvinyl alcohol aqueous solution is 1.0%.

[0167] A method for preparing a metal and porous ceramic dual-phase composite material comprises the following steps:

[0168] 1. Pretreatment and powder mixing;

[0169] The ultrafine quartz powder, sintering aid CaF2, nickel-iron alloy powder, Si powder, boron powder, low-temperature glass powder and inorganic pore-forming agent are mixed, and the mixed powder is obtained after being fully mixed by low-speed ball milling; the mesh size of the sintering aid CaF2, nickel-iron alloy powder, Si powder, boron powder and low-temperature glass powder is 300 mesh.

[0170] 2. Porous ceramic molding;

[0171] The mixed powder is mixed with a polyvinyl alcohol aqueous solution, stirred and mixed evenly, and then formed by dry pressing to obtain a ceramic green body;

[0172] 3. Low temperature sintering;

[0173] The ceramic embryo was dried in a drying oven at 85°C for 4 hours, then heated at a rate of 5°C / min in a vacuum program temperature-controlled furnace to 1150°C and kept for 1 hour, and then cooled to room temperature to obtain a metal and porous ceramic dual-phase composite material.

[0174] Comparative Examples 1-8 are set as follows based on Example 1:

[0175] Comparative Example 1

[0176] A metal and porous ceramic dual-composite phase composite material, comprising the following components per 100 parts by weight:

[0177] 40 parts of diatomaceous earth;

[0178] 5 parts of sintering aid CaF2;

[0179] 4 parts of nickel-iron alloy powder, wherein the content of Ni in the nickel-iron alloy powder is 50wt.%;

[0180] 3 parts of Si powder;

[0181] 8 parts of low temperature glass powder;

[0182] 35 parts of an inorganic pore-forming agent, wherein the inorganic pore-forming agent is SiO2-Al2O3 hollow microspheres with a diameter of 100 μm;

[0183] 5 parts of polyvinyl alcohol aqueous solution, wherein the mass concentration of the polyvinyl alcohol aqueous solution is 1.0%.

[0184] A method for preparing a metal and porous ceramic dual-phase composite material comprises the following steps:

[0185] 1. Pretreatment and powder mixing;

[0186] The diatomaceous earth, sintering aid CaF2, nickel-iron alloy powder, Si powder, low-temperature glass powder and inorganic pore-forming agent are mixed, and then fully mixed by low-speed ball milling to obtain a mixed powder; the mesh size of the sintering aid CaF2, nickel-iron alloy powder, Si powder and low-temperature glass powder is 300 mesh.

[0187] 2. Porous ceramic molding;

[0188] The mixed powder is mixed with a polyvinyl alcohol aqueous solution, stirred and mixed evenly, and then formed by dry pressing to obtain a ceramic green body;

[0189] 3. Low temperature sintering;

[0190] The ceramic embryo was dried in a drying oven at 85°C for 4 hours, then heated at a rate of 5°C / min in a vacuum program temperature-controlled furnace to 1150°C and kept for 1 hour, and then cooled to room temperature to obtain a metal and porous ceramic dual-phase composite material.

[0191] Comparative Example 2

[0192] A metal and porous ceramic dual-composite phase composite material, comprising the following components per 100 parts by weight:

[0193] 40 parts of ultrafine quartz powder;

[0194] 5 parts of sintering aid CaF2;

[0195] 3 parts of Si powder;

[0196] 8 parts of low temperature glass powder;

[0197] 39 parts of an inorganic pore-forming agent, wherein the inorganic pore-forming agent is SiO2-Al2O3 hollow microspheres with a diameter of 100 μm;

[0198] 5 parts of polyvinyl alcohol aqueous solution, wherein the mass concentration of the polyvinyl alcohol aqueous solution is 1.0%.

[0199] A method for preparing a metal and porous ceramic dual-phase composite material comprises the following steps:

[0200] 1. Pretreatment and powder mixing;

[0201] The ultrafine quartz powder, sintering aid CaF2, Si powder, low-temperature glass powder and inorganic pore-forming agent are mixed, and then fully mixed by low-speed ball milling to obtain a mixed powder; the mesh size of the sintering aid CaF2, Si powder and low-temperature glass powder is 300 mesh.

[0202] 2. Porous ceramic molding;

[0203] The mixed powder is mixed with a polyvinyl alcohol aqueous solution, stirred and mixed evenly, and then formed by dry pressing to obtain a ceramic green body;

[0204] 3. Low temperature sintering;

[0205] The ceramic embryo was dried in a drying oven at 85°C for 4 hours, then heated at a rate of 5°C / min in a vacuum program temperature-controlled furnace to 1150°C and kept for 1 hour, and then cooled to room temperature to obtain a metal and porous ceramic dual-phase composite material.

[0206] Comparative Example 3

[0207] A metal and porous ceramic dual-composite phase composite material, comprising the following components per 100 parts by weight:

[0208] 40 parts of ultrafine quartz powder;

[0209] 5 parts of sintering aid CaF2;

[0210] 4 parts of nickel-iron alloy powder, wherein the content of Ni in the nickel-iron alloy powder is 50wt.%;

[0211] 8 parts of low temperature glass powder;

[0212] 39 parts of an inorganic pore-forming agent, wherein the inorganic pore-forming agent is SiO2-Al2O3 hollow microspheres with a diameter of 100 μm;

[0213] 5 parts of polyvinyl alcohol aqueous solution, wherein the mass concentration of the polyvinyl alcohol aqueous solution is 1.0%.

[0214] A method for preparing a metal and porous ceramic dual-phase composite material comprises the following steps:

[0215] 1. Pretreatment and powder mixing;

[0216] The ultrafine quartz powder, sintering aid CaF2, nickel-iron alloy powder, low-temperature glass powder and inorganic pore-forming agent are mixed, and then fully mixed by low-speed ball milling to obtain a mixed powder; the mesh size of the sintering aid CaF2, nickel-iron alloy powder and low-temperature glass powder is 300 mesh.

[0217] 2. Porous ceramic molding;

[0218] The mixed powder is mixed with a polyvinyl alcohol aqueous solution, stirred and mixed evenly, and then formed by dry pressing to obtain a ceramic green body;

[0219] 3. Low temperature sintering;

[0220] The ceramic embryo was dried in a drying oven at 85°C for 4 hours, then heated at a rate of 5°C / min in a vacuum program temperature-controlled furnace to 1150°C and kept for 1 hour, and then cooled to room temperature to obtain a metal and porous ceramic dual-phase composite material.

[0221] Comparative Example 4

[0222] A metal and porous ceramic dual-composite phase composite material, comprising the following components per 100 parts by weight:

[0223] 40 parts of ultrafine quartz powder;

[0224] 5 parts of sintering aid CaF2;

[0225] 4 parts of nickel-iron alloy powder, wherein the content of Ni in the nickel-iron alloy powder is 50wt.%;

[0226] 3 parts of Si powder;

[0227] 8 parts of low temperature glass powder;

[0228] Polystyrene 35 parts;

[0229] 5 parts of polyvinyl alcohol aqueous solution, wherein the mass concentration of the polyvinyl alcohol aqueous solution is 1.0%.

[0230] A method for preparing a metal and porous ceramic dual-phase composite material comprises the following steps:

[0231] 1. Pretreatment and powder mixing;

[0232] The ultrafine quartz powder, sintering aid CaF2, nickel-iron alloy powder, Si powder, low-temperature glass powder and polystyrene are mixed, and then fully mixed by low-speed ball milling to obtain a mixed powder; the mesh size of the sintering aid CaF2, nickel-iron alloy powder, Si powder and low-temperature glass powder is 300 mesh.

[0233] 2. Porous ceramic molding;

[0234] The mixed powder is mixed with a polyvinyl alcohol aqueous solution, stirred and mixed evenly, and then formed by dry pressing to obtain a ceramic green body;

[0235] 3. Low temperature sintering;

[0236] The ceramic embryo was dried in a drying oven at 85°C for 4 hours, then heated at a rate of 5°C / min in a vacuum program temperature-controlled furnace to 1150°C and kept for 1 hour, and then cooled to room temperature to obtain a metal and porous ceramic dual-phase composite material.

[0237] Comparative Example 5

[0238] A metal and porous ceramic dual-composite phase composite material, comprising the following components per 100 parts by weight:

[0239] 40 parts of ultrafine quartz powder;

[0240] 5 parts of sintering aid CaF2;

[0241] 4 parts of nickel-iron alloy powder, wherein the content of Ni in the nickel-iron alloy powder is 50wt.%;

[0242] 3 parts of Si powder;

[0243] 8 parts of low temperature glass powder;

[0244] 35 parts of polymethyl methacrylate;

[0245] 5 parts of polyvinyl alcohol aqueous solution, wherein the mass concentration of the polyvinyl alcohol aqueous solution is 1.0%.

[0246] A method for preparing a metal and porous ceramic dual-phase composite material comprises the following steps:

[0247] 1. Pretreatment and powder mixing;

[0248] The ultrafine quartz powder, sintering aid CaF2, nickel-iron alloy powder, Si powder, low-temperature glass powder and polymethyl methacrylate are mixed, and then fully mixed by low-speed ball milling to obtain a mixed powder; the mesh size of the sintering aid CaF2, nickel-iron alloy powder, Si powder and low-temperature glass powder is 300 mesh.

[0249] 2. Porous ceramic molding;

[0250] The mixed powder is mixed with a polyvinyl alcohol aqueous solution, stirred and mixed evenly, and then formed by dry pressing to obtain a ceramic green body;

[0251] 3. Low temperature sintering;

[0252] The ceramic embryo was dried in a drying oven at 85°C for 4 hours, then heated at a rate of 5°C / min in a vacuum program temperature-controlled furnace to 1150°C and kept for 1 hour, and then cooled to room temperature to obtain a metal and porous ceramic dual-phase composite material.

[0253] Comparative Example 6

[0254] A metal and porous ceramic dual-composite phase composite material, comprising the following components per 100 parts by weight:

[0255] 50 parts of ultrafine quartz powder;

[0256] 6 parts of sintering aid CaF2;

[0257] 8 parts of nickel-iron alloy powder, wherein the content of Ni in the nickel-iron alloy powder is 50wt.%;

[0258] 3 parts of Si powder;

[0259] 8 parts of low-temperature glass powder, wherein the softening point of the low-temperature glass powder is 900° C.;

[0260] 20 parts of an inorganic pore-forming agent, wherein the inorganic pore-forming agent is SiO2-Al2O3 hollow microspheres with a diameter of 100 μm;

[0261] 5 parts of polyvinyl alcohol aqueous solution, wherein the mass concentration of the polyvinyl alcohol aqueous solution is 1.0%.

[0262] A method for preparing a metal and porous ceramic dual-phase composite material comprises the following steps:

[0263] 1. Pretreatment and powder mixing;

[0264] The ultrafine quartz powder, sintering aid CaF2, nickel-iron alloy powder, Si powder, low-temperature glass powder and inorganic pore-forming agent are mixed, and the mixed powder is obtained after being fully mixed by low-speed ball milling; the mesh size of the sintering aid CaF2, nickel-iron alloy powder, Si powder and low-temperature glass powder is 300 mesh.

[0265] 2. Porous ceramic molding;

[0266] The mixed powder is mixed with a polyvinyl alcohol aqueous solution, stirred and mixed evenly, and then formed by dry pressing to obtain a ceramic green body;

[0267] 3. Low temperature sintering;

[0268] The ceramic embryo was dried in a drying oven at 85°C for 4 hours, then heated at a rate of 5°C / min in a vacuum program temperature-controlled furnace to 1150°C and kept for 1 hour, and then cooled to room temperature to obtain a metal and porous ceramic dual-phase composite material.

[0269] Comparative Example 7

[0270] A metal and porous ceramic dual-composite phase composite material, comprising the following components per 100 parts by weight:

[0271] 40 parts of ultrafine quartz powder;

[0272] 5 parts of sintering aid CaF2;

[0273] 2 parts of nickel-iron alloy powder, wherein the content of Ni in the nickel-iron alloy powder is 50wt.%;

[0274] 3 parts of Si powder;

[0275] 8 parts of low-temperature glass powder, wherein the softening point of the low-temperature glass powder is 900° C.;

[0276] 37 parts of an inorganic pore-forming agent, wherein the inorganic pore-forming agent is SiO2-Al2O3 hollow microspheres with a diameter of 100 μm;

[0277] 5 parts of polyvinyl alcohol aqueous solution, wherein the mass concentration of the polyvinyl alcohol aqueous solution is 1.0%.

[0278] A method for preparing a metal and porous ceramic dual-phase composite material comprises the following steps:

[0279] 1. Pretreatment and powder mixing;

[0280] The ultrafine quartz powder, sintering aid CaF2, nickel-iron alloy powder, Si powder, low-temperature glass powder and inorganic pore-forming agent are mixed, and the mixed powder is obtained after being fully mixed by low-speed ball milling; the mesh size of the sintering aid CaF2, nickel-iron alloy powder, Si powder and low-temperature glass powder is 300 mesh.

[0281] 2. Porous ceramic molding;

[0282] The mixed powder is mixed with a polyvinyl alcohol aqueous solution, stirred and mixed evenly, and then formed by dry pressing to obtain a ceramic green body;

[0283] 3. Low temperature sintering;

[0284] The ceramic embryo was dried in a drying oven at 85°C for 4 hours, then heated at a rate of 5°C / min in a vacuum program temperature-controlled furnace to 1150°C and kept for 1 hour, and then cooled to room temperature to obtain a metal and porous ceramic dual-phase composite material.

[0285] Comparative Example 8

[0286] A metal and porous ceramic dual-composite phase composite material, comprising the following components per 100 parts by weight:

[0287] 40 parts of ultrafine quartz powder;

[0288] 5 parts of sintering aid CaF2;

[0289] 4 parts of nickel-iron alloy powder, wherein the content of Ni in the nickel-iron alloy powder is 50wt.%;

[0290] 2 parts of Si powder;

[0291] 8 parts of low-temperature glass powder, wherein the softening point of the low-temperature glass powder is 900° C.;

[0292] 36 parts of an inorganic pore-forming agent, wherein the inorganic pore-forming agent is SiO2-Al2O3 hollow microspheres with a diameter of 100 μm;

[0293] 5 parts of polyvinyl alcohol aqueous solution, wherein the mass concentration of the polyvinyl alcohol aqueous solution is 1.0%.

[0294] A method for preparing a metal and porous ceramic dual-phase composite material comprises the following steps:

[0295] 1. Pretreatment and powder mixing;

[0296] The ultrafine quartz powder, sintering aid CaF2, nickel-iron alloy powder, Si powder, low-temperature glass powder and inorganic pore-forming agent are mixed, and the mixed powder is obtained after being fully mixed by low-speed ball milling; the mesh size of the sintering aid CaF2, nickel-iron alloy powder, Si powder and low-temperature glass powder is 300 mesh.

[0297] 2. Porous ceramic molding;

[0298] The mixed powder is mixed with a polyvinyl alcohol aqueous solution, stirred and mixed evenly, and then formed by dry pressing to obtain a ceramic green body;

[0299] 3. Low temperature sintering;

[0300] The ceramic embryo was dried in a drying oven at 85°C for 4 hours, then heated at a rate of 5°C / min in a vacuum program temperature-controlled furnace to 1150°C and kept for 1 hour, and then cooled to room temperature to obtain a metal and porous ceramic dual-phase composite material.

[0301] The porosity, through-hole diameter and flexural strength of the metal and porous ceramic dual-phase composite materials obtained in the above Examples 1-7 and Comparative Examples 1-8 are shown in Table 1 below:

[0302] Table 1 Porosity, through hole diameter and flexural strength of metal and porous ceramic dual-phase composite materials obtained in Examples 1-7 and Comparative Examples 1-8

[0303] Porosity / % Through hole diameter / um Bending strength / MPa Example 1 53.50 20.56 182 Example 2 51.75 18.95 226 Example 3 55.65 22.78 180 Example 4 50.85 16.35 207 Example 5 51.05 18.25 219 Example 6 51.35 18.38 216 Example 7 51.15 18.65 238 Comparative Example 1 49.05 16.56 152 Comparative Example 2 58.45 25.60 158 Comparative Example 3 60.25 27.11 163 Comparative Example 4 35.25 10.85 246 Comparative Example 5 32.89 10.51 255 Comparative Example 6 45.05 15.66 215 Comparative Example 7 54.00 20.76 162 Comparative Example 8 53.60 20.33 165

[0304] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or replacements within the technical scope disclosed by the present invention, and these modifications or replacements should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.

Claims

1. A metal and porous ceramic dual-phase composite material, characterized in that: Each 100 parts by weight includes the following components: 35-50 parts of ultrafine quartz powder or ultrafine alumina ceramic powder; 3-6 parts of burning aid; 3-8 parts of metal alloy powder; the metal alloy powder is iron-chromium alloy powder, the mesh number of the metal alloy powder is 300-400 mesh, and the content of Cr in the iron-chromium alloy powder is 50-65wt.%; 3-5 parts of Si powder and / or boron powder; 8-15 parts of low-temperature glass powder; the softening point of the low-temperature glass powder is 700-900°C; 25-40 parts of an inorganic pore-forming agent, wherein the inorganic pore-forming agent is SiO2-Al2O3 hollow microspheres; the diameter of the SiO2-Al2O3 hollow microspheres is 100-200 μm, and the impurity content is less than 1%; 5-7 parts of polyvinyl alcohol aqueous solution, wherein the mass concentration of the polyvinyl alcohol aqueous solution is 0.9-1.0%.

2. The metal and porous ceramic dual-phase composite material according to claim 1, characterized in that: The sintering aid is selected from at least one of CaF2 and CaCO3.

3. The metal and porous ceramic dual-phase composite material according to claim 1, characterized in that: The mass fraction of SiO2 in the ultrafine quartz powder is greater than 99%, and the mesh number of the ultrafine quartz powder is less than 300 meshes.

4. The metal and porous ceramic dual-phase composite material according to claim 1, characterized in that: The purity of the ultrafine alumina ceramic powder is greater than 99%, and the mesh number of the ultrafine alumina ceramic powder is less than 300 meshes.

5. The method for preparing the metal and porous ceramic dual-phase composite material according to claim 1, characterized in that: The following steps are involved: S1, pretreatment and powder mixing: adding sintering aid, metal alloy powder, Si powder or B powder, low-temperature glass powder and inorganic pore-forming agent to ultrafine quartz powder or alumina ceramic powder, and then performing low-speed ball milling to fully mix to obtain a mixed powder; S2, porous ceramic molding; the mixed powder is mixed with a polyvinyl alcohol aqueous solution, stirred and mixed evenly, and then molded by dry pressing to obtain a ceramic embryo; the dry pressing molding pressure is 400-600MPa, and the holding time is 5-10min; S3, sintering molding; drying the ceramic green body at 70-90 ° C for 4-6 hours, and then sintering at a vacuum degree of 1*10 -1 The temperature is raised at a rate of less than 5°C / min under vacuum conditions below Pa, kept at 1100-1200°C for 0.5-1h, and cooled to room temperature along with the furnace to obtain a metal and porous ceramic dual-phase composite material.

Citation Information

Patent Citations

  • Metallized porous ceramic composite material and preparation method thereof

    CN115819110A

  • Ceramic porous body and preparing method thereof

    KR1020120088956A